Does the noise in my head bother you? : a rock 'n' roll memoir - Tyler, Steven, 1948-; Dalton, David, 1945- (New York : Ecco Press, 2011)
The frontman of the classic rock band Aerosmith tells his story, including his rise to rock stardom in the 1970s, the band's drop in popularity, and their comeback in the late 1980s and 1990s.
Semiprologue -- Peripheral visionary -- Zits and tits -- The pipe that was never played -- My red parachute (and other dreams) -- Confessions of a rhyme-a-holic -- Little Bo Peep, the glitter queen, and the girl in the yellow Corvette -- Noise in the attic (snow days) -- Ladies and genitals...I'm not a bad guy (just egotestical) -- The hood, the bad, the ugly...hammered with Hemingway -- Food poisoning at a family picnic -- Getting lost on your way to the middle -- Where you end and I begin...again (the goddess) -- Trouble in Paradise (losing your grip on the life fantastic) -- The bitch goddess of Billboard -- Holy smoke, quest for the Grand Pashmina, and the big chill of twenty summers -- To Zanzibar and back -- Falling in love is hard on the knees -- Take a walk inside my mind....
Includes index.
Keywords: Tyler, Steven, -- 1948-; Aerosmith (Musical group); Rock musicians -- United States -- Biography; Rock groups -- United States -- Biography; Singers -- Biography